Ten years in force of the General Administrative Procedure Law: progress - Maraví Sumar, Milagros (2011)
In this article the author analyzes what happened in these ten years regarding issues such as administrative procedure principles, administrative simplification, sanctioning proceedings, administrative site diffuse control and administrative silence.